The Chinese on the Australian goldfields - Hirst, J. B. (John Bradley), 1942-2016. (Melbourne : Dept. of History, La Trobe University, 1991)
Chinese in Australian goldfields
Bibliography: p. 32.
Keywords: Chinese -- Australia -- History; Gold mines and mining -- Australia -- History; Australia -- History -- 1851-1891.